Identification and cross-validation of genetic loci conferring resistance to Septoria nodorum blotch using a German multi-founder winter wheat population - Lin, Min; Stadlmeier, Melanie; Mohler, Volker; Tan, Kar-Chun; Ficke, Andrea; Cockram, James; Lillemo, Morten (Springer, 2020)
© The Author(s).